الفن التشكيلي المعاصر (Journal of Humanitarian and Applied Sciences, 2023)
In this research, I will discuss everything related to contemporary art, including its concept and importance, and introduce the artists of this art, their artistic methods, and the materials used. It also addresses the reasons for the emergence and difference of this art from its predecessor, “modern art.” The contemporary art dates from “the beginning of the second half of the twentieth century,”The research problem is in defining contemporary art, its artists, their artistic methods, and the materials used. The research aims to explore the motivation and inspiration of the artists for contemporary art. The research also aims to monitor the most important contemporary artistic movements and the artist’s ability in creativity and innovation. It also aims to gain insight into contemporary artists and their artistic works. The researcher follows the descriptive and analytical approach to contemporary artistic movements.The research has dealt with the beginnings of contemporary art, and its concept, and features, which made it a distinctive art from the others according to the style, material, etc. One of the most important features of this art is the exhibition of the artist’s feelings and their attempts to eliminate the problems of daily life due to chaos and lack of discipline. Artworks are displayed in courtyards and open spaces not inside exhibition halls. Therefore, it plays an important role in developing the aesthetic concepts and behavior of human beings to lead them to a healthy and unique personality in creativity and imagination. The research ends up with the most important contemporary artistic movements and their place of emergence, such as conceptual art, land art, installation art movement art, and others, and getting to know some artists and their artistic works.